2009
DOI: 10.1021/bi9009242
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Structural Investigations of the Allosteric Site in Human Epithelial 15-Lipoxygenase-2

Abstract: Allosteric regulation of human lipoxygenase (hLO) activity has recently been implicated in the cellular biology of prostate cancer. In the current work, we present isotope effect, pH and substrate inhibitor data of epithelial 15-hLO-2, which probe the allosteric effects on its mechanistic behavior. The Dkcat/KM for 15-hLO-2, with AA and LA as substrate, is large indicating hydrogen atom abstraction is the principle rate-determining step, involving a tunneling mechanism for both substrates. For AA, there are mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 59 publications
10
80
0
Order By: Relevance
“…Though, different reaction kinetics for both quaternary structures are conceivable, similarly to what was already discussed for 12-LO (Aleem et al , 2008 ) and 15-LO2 (Wecksler et al , 2009 ). An impact of dimerization on the reaction kinetics is presumable due to the observation that the predicted dimer interface is located at the proposed substrate and oxygen entry site of LOs (Ivanov et al , 2010 ).…”
Section: Discussionsupporting
confidence: 62%
“…Though, different reaction kinetics for both quaternary structures are conceivable, similarly to what was already discussed for 12-LO (Aleem et al , 2008 ) and 15-LO2 (Wecksler et al , 2009 ). An impact of dimerization on the reaction kinetics is presumable due to the observation that the predicted dimer interface is located at the proposed substrate and oxygen entry site of LOs (Ivanov et al , 2010 ).…”
Section: Discussionsupporting
confidence: 62%
“…The substrate preference obtained for the WT is similar to the one calculated from the kinetic constants ( 18 ), underlining the accuracy of the method used. It also indicates that there are probably no substrate/product allosteric interactions as seen with lipoxygenase ( 29 ). While the total amount of diol formed by each SNP was different, the relative amounts of diol among the different EpFA substrates were similar (supplementary Fig.…”
Section: Selectivity For Epfasmentioning
confidence: 94%
“…It is unclear if these responses are due to effects on the transcriptional regulation of the associated enzymes, or if this is a result from direct effects on enzyme activity. However, it has been shown that LOX metabolites of ARA and LA can differentially affect the substrate selectivity [129] and reaction mechanism [130] of the LOX enzymes through allosteric regulation. This suggests a direct protein/metabolite interaction may regulate crosstalk within the ARA cascade, and that metabolite interactions may extend into other pathways such LA and ω-3 fatty acids metabolizing cascades.…”
Section: Crosstalk Between Pathways In the Ara Cascadementioning
confidence: 99%